Bison with benefits: towards integrating wildlife and ranching sectors on a public rangeland in the western USA. Issue 3 (8th May 2015) - Ranglack, Dustin H.; du Toit, Johan T.
Abstract: The North American model of wildlife conservation, based on the public trust doctrine, is credited for the recovery of several charismatic wildlife species, including the plains bison Bison bison . In that model, wildlife is a public resource from which the private sector may not profit either individually or collectively. In recent years, however, resilience thinking is driving changes in the traditional state-run wildlife management model to allow for integrated multi-sector approaches at the landscape scale. A free-ranging herd of bison on public land in the Henry Mountains of Utah is used as a case study to consider if and how a community-based conservation programme could be developed for a state-managed wildlife resource to benefit all stakeholders. The Henry Mountains bison, which are disease-free, share the rangeland with cattle that are privately owned by individual ranchers and corporations with various economic goals and environmental values. The ranchers currently derive no benefits from the bison and have concerns regarding competition between bison and cattle. However, a threshold harvesting strategy with community participation could generate revenue to offset these concerns. It could also provide benefits to the local community, increase state revenue, and increase the size of the bison population while securing its long-term genetic viability. Implementation would initially require facilitation by policy specialists, after which we suggest a Henry Mountains bison partnership could serve as a model for bison recovery efforts elsewhere in North America.